Estudio de prefactibilidad para la instalación de una planta para la elaboración de pañales desechables de bambú - Peña Morales, Milenka Milagros (2023)
This research developed a pre-feasibility study for the installation of a plant for the production of disposable bamboo diapers, which demonstrated its technical, economic and social viability. The project began by defining that the commercialization of disposable diapers is one of the causes of environmental pollution in Peru, since it is a good that generates a large amount of non-biodegradable waste per year per baby. That is why it was proposed as a sustainable alternative to disposable bamboo diapers. For which, the target audience of the project was determined to be parents with children between 0 and 3 years of socioeconomic levels A, B and C1 located in Metropolitan Lima and provinces. On the other hand, the demand for the project was defined taking into account the DIA, the demographic and socioeconomic segmentation and finally the taking of the market, with which it was concluded that the value of the demand for this project is 55 503 499 units of diapers. After that, the location of the company was determined taking into account factors of macro location and micro location (availability of raw material, proximity to the target market, availability of land, among others) considering the most appropriate alternative to the Callao district. The capacity of the production plant was also found, for which a material balance was carried out, the number of operators, machines and working hours were determined. Once these data were obtained, the capacity of the plant was calculated based on the limiting operations, which correspond to packaging and sealing, with a production of 2 344 742 packages/year. Finally, the economic and financial viability of the project was established from a total investment of S/ 13 472 009 distributed at 40% in own capital and the remaining percentage with a loan of constant installments with TEA of 17,00%. Said data, allowed to obtain at an economic level a NPV of S/ 10 787 037, an IRR of 40,10% and a benefit/cost ratio of 1,88; On the other hand, at a financial level, a NPV of S/ 11 883 883 was obtained, an IRR of 61,96% and a benefit/cost ratio of 3,21. Therefore, it is concluded that the project of the bamboo ecological diaper production plant is viable.